2022
DOI: 10.3390/antibiotics11101275
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Drug Resistant Pathogenic Escherichia coli Isolated from Wild Birds, Chicken, and the Environment in Malaysia

Abstract: Transmission of pathogenic microorganisms in the last decades has been considered a significant health hazard and pathogenic E. coli, particularly antibiotic-resistant strains, have long been identified as a zoonotic problem. This study aimed to investigate multidrug resistant pathogenic E. coli isolates from wild birds, chickens, and environment in selected Orang Asli and Malay villages in Peninsular Malaysia. The bacteriological culture-based technique, disc diffusion method, and multiplex Polymerase Chain R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Animal waste, sewage from farming operations, manure/slurries used as fertilizers or for silage preparation, and livestock grazing contribute to the infection and reinfection of livestock. The presence of E. coli in the soil promotes its spread among livestock, and its presence in the environment poses a risk of human infections (Mohamed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal waste, sewage from farming operations, manure/slurries used as fertilizers or for silage preparation, and livestock grazing contribute to the infection and reinfection of livestock. The presence of E. coli in the soil promotes its spread among livestock, and its presence in the environment poses a risk of human infections (Mohamed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These serotypes are responsible for foodborne infections in both livestock and humans and are referred to as zoonotic E. coli. The detection of Shiga-like toxins is a valuable tool for identifying entero-hemorrhagic E. coli strains (Vieira, 2010;Mohamed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Hasan et al [ 223 ] discovered that E. coli isolated from both domestic and wild birds was most commonly resistant to tetracycline, ampicillin, trimethoprim/sulfamethoxazole, and nalidixic acid, while Nowaczek et al [ 224 ] found E. coli isolated from free-living birds to be resistant to gentamicin too. On average, MDR was found in 42.7% of the isolates obtained from avian samples [ 223 , 224 , 225 , 226 ]. In the treatment of infections caused by E. coli , such as those acquired in the community or a hospital setting, the typical approach has been to use first-line antibiotics.…”
Section: Antimicrobial Resistance Profiles Of Bacteria Isolated From ...mentioning
confidence: 99%
“…An increase in STEC antibiotic resistance is another major issue that we are facing currently. STEC resistant to various broad-spectrum antibiotics has been isolated from livestock, wildlife sources, and the environment [30,67,177,178]. The use of antibiotic growth promoters (AGPs) has further enhanced this problem of antibiotic resistance in STEC.…”
Section: Rise In Antibiotic-resistant Strainsmentioning
confidence: 99%